2020
DOI: 10.21037/atm-20-225
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable high-purity magnesium interbody cage: degradation, interbody fusion, and biocompatibility from a goat cervical spine model

Abstract: Background: Bioabsorbable Mg-based implants have been a focus of orthopedic researches due to their intrinsic advantages in orthopedics surgeries. This study aimed to investigate the performance of bioabsorbable high-purity magnesium (HP Mg, 99.98 wt.%) interbody cages in anterior cervical discectomy and fusion (ACDF) and to evaluate the degradation of HP Mg cages under an interbody microenvironment.Methods: ACDF was performed at C2-3 and C4-5, and a HP Mg cage or autologous iliac bone was randomly implanted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…After 24 weeks, new bone tissue between endplates in graft segments was found in CT 3D reconstruction images (Figure 5B), while no fusion with a cage was observed (Figure 5C). ACDF surgery on a goat model, and achieved the first successful interbody fusion, indicating the possibility of Mgbased cage application in ACDF (8). However, this study also reported that the total area of interbody fusion was less than 30%.…”
Section: Fusion Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…After 24 weeks, new bone tissue between endplates in graft segments was found in CT 3D reconstruction images (Figure 5B), while no fusion with a cage was observed (Figure 5C). ACDF surgery on a goat model, and achieved the first successful interbody fusion, indicating the possibility of Mgbased cage application in ACDF (8). However, this study also reported that the total area of interbody fusion was less than 30%.…”
Section: Fusion Resultsmentioning
confidence: 58%
“…Potential reasons include that co-implantation of titanium and Mg accelerates degradation of Mg cages, and hydrogen and excessively increasing pH value produced by rapid Mg corrosion negatively influence surrounding tissues healing. Recently, Guo et al claimed that they achieved histological fusion of HP-Mg cages in a goat model, although total fusion area was less than 30% (8).…”
Section: Original Articlementioning
confidence: 99%
“…The fusion rates in control group of our study were 41.7% (5/12) and 58.3% (7/12) at 12 and 24 weeks, respectively. In other studies, which used the same criteria for the evaluation of interbody fusion based on CT scoring in goat model, autologous iliac bone with titanium plate and screws fixation was performed as the control group and the fusion scores both in 12 and 24 weeks were higher than the present study [28,29]. Another goat study used PEEK cage filled with an autologous graft in the control group and 2/6 indicated arthrodesis with solid bone bridging the fusion area through radiographic analysis after 12 weeks [7].…”
Section: Discussionmentioning
confidence: 54%
“…Through degradation, interbody fusion, and biocompatibility testing of a goat cervical vertebra model, Guo et al found that Mg-based interbody fusion cage had better histological fusion, but the total fusion area needed to be improved. This is the first report of successful histological fusion of a Mg-based interbody fusion cage ( Guo et al, 2020 ). The main obstacle to limiting the clinical application of Mg-based cages is the adverse reactions caused by the rapid degradation of Mg.…”
Section: Interbody Fusion Cage Materialsmentioning
confidence: 88%
“…The most commonly used interbody cages are made of non-absorbent materials, such as titanium (Ti) and poly-ether-ether-ketone (PEEK). Ti alloy may cause implant subsidence and segmental instability due to its high elastic modulus, and the use of PEEK is limited due to its poor biocompatibility leading to chronic inflammatory responses ( Guo et al, 2020 ). Absorbable materials include magnesium (Mg) and other polymer materials.…”
Section: Introductionmentioning
confidence: 99%